2023
DOI: 10.1186/s12889-023-16290-7
|View full text |Cite
|
Sign up to set email alerts
|

The crowding-out effect of sugar-sweetened beverages (SSBs) on household expenditure patterns in Bangladesh

Abstract: Background Consumption of sugar-sweetened beverages (SSBs) or sugary drinks may reduce or even eliminate the household income allocation for other essential commodities. Reducing expenditure for consumption of other household commodities is known as the crowding-out effect of SSB. We aimed to determine the crowding-out effect of SSB expenditure on other household commodities. In addition, we also identified the factors influencing the household's decision to purchase of SSBs. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It was also found that the consumption of SSB was higher among older adolescent boys (15-19 years) compared to younger adolescent boys; however, SSB consumption was reported lower among older girls compared to their younger counterparts [14]. Our recent study shows that the household expenditure on beverages and sugaradded drinks is around 2% of monthly household expenditure, however, the spending on beverages and sugar-added drinks is alarming due to the displacement of household expenditure for essential commodities including food, clothing, housing, education, and energy [15].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…It was also found that the consumption of SSB was higher among older adolescent boys (15-19 years) compared to younger adolescent boys; however, SSB consumption was reported lower among older girls compared to their younger counterparts [14]. Our recent study shows that the household expenditure on beverages and sugaradded drinks is around 2% of monthly household expenditure, however, the spending on beverages and sugar-added drinks is alarming due to the displacement of household expenditure for essential commodities including food, clothing, housing, education, and energy [15].…”
Section: Introductionmentioning
confidence: 84%
“…The SSBs can generally be defined as sugar-added drinks. Sugar-added drinks may encompass sugar-added soft drinks, carbonated drinks, sugary fruit drinks, sugary soda, and sweetened water [15,20]. Allcott et al (2019) emphasized on tea and coffee to be included in the definition of SSBs if additional sugar is added to tea and coffee [21].…”
Section: Data and Variablesmentioning
confidence: 99%
See 3 more Smart Citations